Effects of nitrate supplements on cardiopulmonary fitness at high altitude: A meta-analysis of nine randomized controlled trials - Chao Kang; Ning Lin; Yanle Xiong; Yi Yang; Jiaojiao Shi; Kaihong Zeng; Xin Ma (PLoS ONE, 2025)
Background Nitrate is a dietary intervention commonly used to enhance exercise capacity, including cardiopulmonary fitness, yet its effectiveness has been recently questioned at high altitudes. This meta-analysis systematically evaluates the effects of dietary nitrate supplements on cardiopulmonary fitness at high altitude, as reflected in the biomarker of cardiopulmonary fitness, paving the way for informed dietary strategies. Methods We conducted a systematic assessment and meta-analysis of randomized controlled trials to examine the effects of dietary nitrate supplementation on biomarkers of cardiorespiratory health at high altitude. Studies were included if they involved healthy individuals (≥16 years of age) engaging in endurance activities such as hiking, long-distance running, mountain climbing, or bicycling at high altitude. Outcomes of interest included nitrite levels (NO2-), maximal oxygen uptake (VO2max), heart rate (HR), perceived exertion (RPE), and pulse oxygen saturation (SpO2). Exclusion criteria included duplicate publications, non-human studies, studies with missing data that could not be retrieved, non-randomized clinical trials, and non-original research articles such as conference papers, expert consensus, or reviews. Our search for articles was conducted across PubMed, Scopus, Web of Science, and Embase, without any language restrictions. A random effects model was employed for quantitative data analysis, utilizing Standardized Mean Difference (SMD) and 95% confidence intervals as summary statistics. The methods and results were reported according to the PRISMA2020 statement. Results A total of 9 studies with a sample size of 161 cases were included in the analysis. The meta-analysis indicated that dietary nitrate supplement significantly elevated NO2- concentration (95% CI: 1.38 to 3.12; SMD = 2.25, P < 0.00001; I2 = 70%). However, there was no significant effect observed on VO2max (95% CI: -0.58 to 0.23; SMD = -0.17, P = 0.76; I2 = 0%), HR (95% CI: -0.31 to 0.23; SMD = -0.04, P = 0.77; I2 = 0%), RPE scores (95% CI: -0.49 to 0.18; SMD = -0.16, P = 0.36; I2 = 0%), and SpO2 percentage (95% CI: -0.36 to 0.20; SMD = -0.08, P = 0.58; I2 = 0%). Conclusions The current meta-analysis indicates that dietary nitrate intake is less correlated with cardiopulmonary fitness at high altitudes, and further research is required to clarify its impact on exercise capacity.